Analysis of Competition Law on Alleged Monopolistic Practices in The Sale of Fuel Oil (BBM) by PT Pertamina (Persero) in Indonesia - Amanda; Aurelia Denise; Catherine Vellynia Samudra (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2025)
This study aims to analyze the alleged monopolistic practices carried out by PT Pertamina (Persero) in the distribution and sale of Fuel Oil (BBM) in Indonesia. The analysis is carried out through the perspective of business competition law as regulated in Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. PT Pertamina (Persero), through its subsidiary, PT Pertamina Patra Niaga, is known to control more than 95% of the national BBM market share, this dominance raises concerns about the creation of unfair business competition, especially for private companies that are also engaged in the BBM distribution sector such as PT Vivo Energy Indonesia. The research method used is normative juridical with a statutory and conceptual approach, and is analyzed qualitatively to gain an in-depth understanding of the issues studied. The results of the study indicate that significant market dominance by PT Pertamina (Persero), accompanied by government intervention in setting BBM prices, and the existence of barriers to market entry for competitors are strong indications of hidden monopolistic practices that violate the principles of fair competition. The role of the Business Competition Supervisory Commission (KPPU) as an institution authorized to supervise and enforce business competition law, still faces structural challenges in carrying out effective and optimal supervision. Therefore, this study emphasizes the importance of strict enforcement of business competition law, as well as the need for policy reform, to realize the principles of economic democracy and consumer protection.